The α-Gal epitope - the cause of a global allergic disease - Perusko, Marija; Grundström, Jeanette; Eldh, Maria; Hamsten, Carl; Apostolovic, Danijela; van Hage, Marianne (Frontiers in Immunology, 2024)
The galactose-α-1,3-galactose (α-Gal) epitope is the cause of a global allergic disease, the α-Gal syndrome (AGS). It is a severe form of allergy to food and products of mammalian origin where IgE against the mammalian carbohydrate, α-Gal, is the cause of the allergic reactions. Allergic reactions triggered by parenterally administered α-Gal sources appear immediately, but those triggered by oral route appear with a latency of several hours. The α-Gal epitope is highly immunogenic to humans, apes and old-world monkeys, all of which produce anti-α-Gal antibodies of the IgM, IgA and IgG subclasses. Strong evidence suggests that in susceptible individuals, class switch to IgE occurs after several tick bites.In this review, we discuss the strong immunogenic role of the α-Gal epitope and its structural resemblance to the blood type B antigen. We emphasize the broad abundance of α-Gal in different foods and pharmaceuticals and the allergenicity of various α-Gal containing molecules. We give an overview of the association of tick bites with the development of AGS and describe innate and adaptive immune response to tick saliva that possibly leads to sensitization to α-Gal. We further discuss a currently favored hypothesis explaining the mechanisms of the delayed effector phase of the allergic reaction to α-Gal. We highlight AGS from a clinical point of view. We review the different clinical manifestations of the disease and the prevalence of sensitization to α-Gal and AGS.The usefulness of various diagnostic tests is discussed. Finally, we provide different aspects of the management of AGS. With climate change and global warming, the tick density is increasing, and their geographic range is expanding. Thus, more people will be affected by AGS which requires more knowledge of the disease.